2004
DOI: 10.1213/01.ane.0000130023.48259.fb
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Tunneling of Caudal Catheters Reduces the Rate of Bacterial Colonization to That of Lumbar Epidural Catheters

Abstract: Bacterial colonization is regarded as a causative factor for septic complications of caudal catheters in children. To determine whether tunneling caudal catheters reduces the bacterial colonization rate effectively, we evaluated 506 children being treated with tunneled or untunneled caudal or untunneled lumbar epidural catheters. Four-hundred-nine children completed the study. After aseptic removal, the catheters were cultured and sent for microbiological assessment. We found a bacterial colonization rate of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 18 publications
0
29
0
5
Order By: Relevance
“…As the rate of catheter colonisation by bacteria is higher in caudal catheters, we prefer the thoracic approach to epidural analgesia. (11,12) To the best of our knowledge, there are few studies on epidural analgesia in young children. Earlier studies of neuraxial techniques used on infants arose from a need to avoid general anaesthesia in high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…As the rate of catheter colonisation by bacteria is higher in caudal catheters, we prefer the thoracic approach to epidural analgesia. (11,12) To the best of our knowledge, there are few studies on epidural analgesia in young children. Earlier studies of neuraxial techniques used on infants arose from a need to avoid general anaesthesia in high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…No presente estudo não foi encontrado nenhum caso. Wang e col. estimaram a incidência de abcesso peridural em 0,05% e a porcentagem de colonização de cateteres colocados no espaço peridural varia entre 5,8% e 45,8% [25][26][27] . Capdevila e col. e Morin e col. encontraram porcentagens de colonização de 28,7% e 23,5% 16,28 .…”
Section: Discussionunclassified
“…Nerve lesions were not observed in the present study. Wang et al estimated a 0.05% incidence of epidural abscess, and between 5.8 and 45.8% incidence of bacterial colonization of epidural catheters [25][26][27] . Capdevilla et al and Morin et al reported colonization rates of 28.7% and 23.5% 16,28 .…”
Section: Discussionmentioning
confidence: 99%
“…In their study, a total of 22 catheters were found to be colonized by pathogens out of which 14 catheters were taped and 8 were tunneled. Bubeck et al 13 reported a reduced colonization caudal catheters in children if tunneled. No evidence of erythema or bacterial contamination of catheter tip was encountered in our study.…”
Section: Riamentioning
confidence: 99%